2021
DOI: 10.1007/s10067-021-05692-w
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Multisystem inflammatory syndrome in children during the COVID-19 pandemic in Turkey: first report from the Eastern Mediterranean

Abstract: The authors regrets that In the original published version of this article one co-author "İlker Ertugrul" was inadvertently omitted in the authorship section. The author name has been added above. The original article has been corrected. Publisher's note Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Some studies reported that there is a slight male predominance in MIS-C cases, 14 15 22 26 while others found slightly more female predisposition of MIS-C. 16 24 25 Our study did not find any gender predisposition which was similar to the other studies by Belhadjer et al, 27 Tiwari et al, 28 and Baradaran et al 29 Therefore, considering the data currently available, it cannot be opined that the probability of developing MIS-C is directly related with the sex of the patients. In our study, patients most frequently presented with persistent fever (100%), which is similar to findings in other studies about MIS-C. 15 23 30 31 32…”
Section: Discussionsupporting
confidence: 91%
“…Some studies reported that there is a slight male predominance in MIS-C cases, 14 15 22 26 while others found slightly more female predisposition of MIS-C. 16 24 25 Our study did not find any gender predisposition which was similar to the other studies by Belhadjer et al, 27 Tiwari et al, 28 and Baradaran et al 29 Therefore, considering the data currently available, it cannot be opined that the probability of developing MIS-C is directly related with the sex of the patients. In our study, patients most frequently presented with persistent fever (100%), which is similar to findings in other studies about MIS-C. 15 23 30 31 32…”
Section: Discussionsupporting
confidence: 91%